Asphalt Composition

The asphalt composition, featuring a specific polyester polycondensate and mixed with asphalt and aggregate, addresses the challenges of rutting and storage stability, achieving effective suppression of rutting and maintaining high-temperature stability.

JP7653212B2Active Publication Date: 2025-03-28KAO CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2021035330
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-03-06
Filing Date
2021-03-05
Publication Date
2025-03-28
Estimated Expiration
2041-03-05

AI Technical Summary

Technical Problem

Existing asphalt compositions with polyester struggle to simultaneously suppress rutting on pavement surfaces and maintain storage stability at high temperatures.

Method used

An asphalt composition is developed containing polyester as a polycondensate of polyethylene terephthalate, an alcohol, and a carboxylic acid compound, with an alkylene oxide adduct of bisphenol A, which is mixed with asphalt and aggregate to form a stable and rutting-resistant asphalt mixture.

Benefits of technology

The proposed asphalt composition achieves excellent storage stability and effectively suppresses rutting on pavement surfaces, addressing the limitations of prior art by maintaining performance under high-temperature conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007653212000001
    Figure 0007653212000001
  • Figure 0007653212000002
    Figure 0007653212000002
  • Figure 0007653212000003
    Figure 0007653212000003
Patent Text Reader

Abstract

To provide an asphalt composition that has excellent storage stability and can prevent rutting of a paved surface after construction, an asphalt mixture and a method for producing the same.SOLUTION: The present invention provides an asphalt composition containing asphalt and a polyester, wherein the polyester is a polycondensate of polyethylene terephthalate, an alcohol, and a carboxylic compound. The alcohol includes an alkylene oxide adduct of bisphenol A.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an asphalt composition, an asphalt mixture and a method for producing the same, and a method for paving roads. [Background technology]

[0002] 2. Description of the Related Art Asphalt pavement using an asphalt composition is used for paving roads, parking lots, freight yards, sidewalks, etc. because it is relatively easy to lay and the time from the start of paving work to the start of traffic is short. Asphalt pavement has a road surface formed from an asphalt mixture in which aggregate is bound with asphalt, so the paved road has good hardness and durability. However, asphalt pavement surfaces develop ruts and cracks over time, making it necessary to repair the pavement, which increases maintenance costs and has a significant impact on automobile traffic.

[0003] Patent Document 1 discloses a method for producing a plastic composition for paving material, in which waste PET is transesterified with one or more polyhydric alcohols and / or sugars in the presence of a catalyst to obtain a plastic composition for paving material, with the aim of enabling waste PET to be processed in large quantities at the lowest possible cost and providing an expensive plastic composition for paving material with desired properties.

[0004] Meanwhile, Patent Document 2 discloses an asphalt composition for road paving that has excellent dry strength, water immersion strength, and petroleum immersion strength, and the asphalt composition for road paving contains asphalt, polyester resin, and aggregate, the polyester resin being a polyester having structural units derived from an alcohol component containing 65 mol% or more of an alkylene oxide adduct of bisphenol A and structural units derived from a carboxylic acid component containing 50 mol% or more of one or more selected from the group consisting of terephthalic acid and isophthalic acid, the softening point being 95°C or more and 130°C or less, and the hydroxyl value being 20 mgKOH / g or more and 50 mgKOH / g or less, and the ratio of the polyester resin being 5 parts by mass or more and 50 parts by mass or less per 100 parts by mass of the asphalt. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2006-096799 A [Patent Document 2] International Publication No. 2017 / 125421 Summary of the Invention [Problem to be solved by the invention]

[0006] Conventionally, when a composition containing asphalt and polyester is used, an asphalt composition with high dry strength is obtained, but there is a demand for an asphalt composition that can further suppress rutting on the pavement surface after construction. In addition, in conventional techniques, it is difficult to simultaneously suppress rutting and ensure the storage stability of the asphalt composition at high temperatures. For example, the technique of Patent Document 2 can suppress rutting, but has a problem with the storage stability of the asphalt at high temperatures. The present invention relates to an asphalt composition, an asphalt mixture, and a method for producing the same, which have excellent storage stability and can suppress rutting on a paved surface after construction. [Means for solving the problem]

[0007] The present invention relates to the following [1] to [4]. [1] An asphalt composition containing asphalt and polyester, The asphalt composition, wherein the polyester is a polycondensate of polyethylene terephthalate, an alcohol, and a carboxylic acid compound, and the alcohol comprises an alkylene oxide adduct of bisphenol A. [2] Step 1: A step of subjecting polyethylene terephthalate, an alcohol component containing a bisphenol A alkylene oxide adduct, and a carboxylic acid component to a polycondensation reaction in the presence of an esterification catalyst to obtain a polyester; and Step 2: Mixing asphalt with the polyester obtained in step 1 A method for producing an asphalt composition comprising the steps of: [3] An asphalt mixture comprising the asphalt composition according to [1] above and aggregate. [4] Step 1: A step of obtaining a polyester by polycondensation reaction of polyethylene terephthalate, an alcohol component containing a bisphenol A alkylene oxide adduct, and a carboxylic acid component in the presence of an esterification catalyst; and Step 2: Mixing the heated aggregate, asphalt, and the polyester obtained in step 1 A method for producing an asphalt mixture comprising the steps of: Effect of the Invention

[0008] According to the present invention, it is possible to provide an asphalt composition, an asphalt mixture, and a method for producing the same, which have excellent storage stability and can suppress rutting on a paved surface after construction. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] [Asphalt composition] The asphalt composition of the present invention (hereinafter also simply referred to as "asphalt composition") contains asphalt and polyester. The polyester is a polycondensate of polyethylene terephthalate, an alcohol and a carboxylic acid compound, and the alcohol contains an alkylene oxide adduct of bisphenol A. According to the above, an asphalt composition having excellent storage stability and capable of suppressing rutting on a pavement surface after construction can be obtained. Furthermore, by applying this technology, an asphalt mixture and a method for producing an asphalt mixture can be provided.

[0010] The reason why the present invention has an advantageous effect is not clear, but is thought to be as follows. If polyethylene terephthalate (hereinafter also referred to as "PET") is added to asphalt as it is without processing, the melting point of PET is relatively high at 260°C, so the PET will remain in the pavement as lumps of its original particle size, which will cause the rut resistance of the asphalt mixture to decrease. Also, a method has been disclosed in which PET oligomers obtained by hydrolyzing PET in an autoclave are added to asphalt, but the molecular weight of the oligomer is low at about 1000, so it does not result in an improvement in rut resistance. In contrast, the polyester used in the present invention is a polycondensate of PET, alcohol and a carboxylic acid compound, and an ester exchange reaction occurs by polycondensing PET with an alcohol component and a carboxylic acid component, resulting in a polyester in which the structural units of PET are incorporated into structural units derived from the alcohol component and structural units derived from the carboxylic acid component. The alcohol component includes an alkylene oxide adduct of bisphenol A. By including an alkylene oxide adduct of bisphenol A having hydrophobicity, the polyester can be finely dispersed in the hydrophobic asphalt. The hydrophilic PET structure incorporated in the polyester while maintaining the fine dispersion state strongly interacts with the asphaltene contained in the asphalt, thereby firmly binding the asphalt and the aggregate, and it is believed that rutting of the pavement surface after construction can be efficiently suppressed. Furthermore, due to the fine dispersion state and the strong interaction between the PET structure and asphaltene, the polyester is less likely to precipitate in the asphalt, and as a result, it is believed that the storage stability is also excellent.

[0011] "Rutting" refers to the flow of the asphalt layer that forms the pavement surface during high temperatures such as summer, resulting in continuous unevenness in the longitudinal direction of the roadway. Rutting is correlated with the plastic flow resistance of the asphalt composition that is the binder of asphalt pavement, and according to the SUPERPAVE binder standard (Japan Road Association, Pavement Testing Method Handbook Supplement, 1996), the G of the asphalt composition (binder) * / sinδ, where G * represents the complex modulus of elasticity, and G * and sin δ are measured with a rheometer. G * The larger the value of / sin δ, the greater the plastic flow resistance, and therefore it is evaluated that the asphalt composition can provide an asphalt pavement with excellent rut resistance.

[0012] The definitions of various terms used in this specification are given below. The term "binder mixture" refers to a mixture containing asphalt and a thermoplastic elastomer, and is a concept that includes, for example, asphalt modified with the thermoplastic elastomer described below (hereinafter also referred to as "modified asphalt"). In the polyester, a "structural unit derived from an alcohol component" means a structure obtained by removing a hydrogen atom from a hydroxyl group of an alcohol component, and a "structural unit derived from a carboxylic acid component" means a structure obtained by removing a hydroxyl group from a carboxyl group of a carboxylic acid component. The term "carboxylic acid compound" is a concept that includes not only the carboxylic acid itself, but also anhydrides that decompose during a reaction to generate an acid, and alkyl esters of carboxylic acids (for example, alkyl groups having 1 to 3 carbon atoms). When the carboxylic acid compound is an alkyl ester of a carboxylic acid, the number of carbon atoms of the alkyl group that is the alcohol residue of the ester is not included in the number of carbon atoms of the carboxylic acid compound.

[0013] 〔asphalt〕 The asphalt composition of the present invention contains asphalt. As the asphalt, various kinds of asphalt can be used. For example, in addition to straight asphalt, which is petroleum asphalt for paving, modified asphalt can be mentioned. Modified asphalt can be blown asphalt; asphalt modified with polymeric materials such as thermoplastic elastomers and thermoplastic resins. Straight asphalt means residual bituminous material obtained by treating crude oil with an atmospheric distillation unit, a vacuum distillation unit, etc. Also, blown asphalt means asphalt obtained by heating a mixture of straight asphalt and heavy oil, and then blowing air into it to oxidize it. From the viewpoint of rut resistance, modified asphalt is preferred, and from the viewpoint of versatility, straight asphalt is preferred. As used herein, "asphalt" includes bitumen as defined in German Industrial Standard DIN EN 12597. "Asphalt" and "bitumen" shall be used interchangeably.

[0014] In the present invention, from the viewpoint of improving rut resistance, the asphalt has an asphalt content of preferably 10 mass% or more, more preferably 15 mass% or more, and preferably 30 mass% or less, more preferably 25 mass% or less, and even more preferably 20 mass% or less, based on 100 mass% of asphalt. The asphaltene content in asphalt is a value measured according to the Japan Petroleum Institute standard JPI-5S-22-83 "Asphaltene Composition Analysis Method by Column Chromatography."

[0015] [Thermoplastic elastomer] From the viewpoint of rut resistance, the asphalt composition preferably contains a thermoplastic elastomer. The asphalt and the thermoplastic elastomer are preferably used as a binder mixture, which is a mixture of these. Examples of the binder mixture include straight asphalt (modified asphalt) modified with a thermoplastic elastomer.

[0016] Examples of the thermoplastic elastomer include at least one selected from the group consisting of styrene / butadiene block copolymer (hereinafter, also referred to as "SB"), styrene / butadiene / styrene block copolymer (hereinafter, also referred to as "SBS"), styrene / butadiene random copolymer (hereinafter, also referred to as "SBR"), styrene / isoprene block copolymer (hereinafter, also referred to as "SI"), styrene / isoprene / styrene block copolymer (hereinafter, also referred to as "SIS"), styrene / isoprene random copolymer (hereinafter, also referred to as "SIR"), ethylene / vinyl acetate copolymer, and ethylene / acrylic acid ester copolymer. An example of a commercially available ethylene / acrylic acid ester copolymer is "Elvaroy" (manufactured by DuPont).

[0017] Among these thermoplastic elastomers, from the viewpoint of improving rut resistance, at least one selected from the group consisting of styrene / butadiene block copolymers, styrene / butadiene / styrene block copolymers, styrene / butadiene random copolymers, styrene / isoprene block copolymers, styrene / isoprene / styrene block copolymers, and styrene / isoprene random copolymers is preferred, and at least one selected from the group consisting of styrene / butadiene random copolymers and styrene / butadiene / styrene block copolymers is more preferred.

[0018] From the viewpoint of improving rut resistance, the content of the thermoplastic elastomer in the asphalt composition is preferably 0.1 mass% or more, more preferably 0.5 mass% or more, even more preferably 1 mass% or more, still more preferably 2 mass% or more, and is preferably 30 mass% or less, more preferably 20 mass% or less, even more preferably 10 mass% or less, and still more preferably 5 mass% or less, based on 100 mass% of the asphalt composition.

[0019] In the asphalt composition, the content of the thermoplastic elastomer is, from the viewpoint of improving rut resistance, preferably 0.1 part by mass or more, more preferably 0.5 part by mass or more, even more preferably 1 part by mass or more, still more preferably 2 parts by mass or more, and preferably 30 parts by mass or less, more preferably 20 parts by mass or less, even more preferably 10 parts by mass or less, and still more preferably 5 parts by mass or less, per 100 parts by mass of asphalt.

[0020] The content of asphalt in the asphalt composition is, from the viewpoint of rut resistance and exhibiting asphalt performance, preferably 60 mass% or more, more preferably 70 mass% or more, even more preferably 75 mass% or more, and even more preferably 80 mass% or more, based on 100 mass% of the asphalt composition; and from the viewpoint of improving rut resistance, the content of asphalt is preferably 98 mass% or less, more preferably 97 mass% or less, and even more preferably 96 mass% or less.

[0021] 〔polyester〕 The asphalt composition of the present invention contains a polyester. From the viewpoint of improving storage stability and rut resistance, the polyester is a polycondensation product of polyethylene terephthalate, an alcohol and a carboxylic acid compound, and the alcohol contains an alkylene oxide adduct of bisphenol A.

[0022] <Alcohol content> From the viewpoint of obtaining excellent rut resistance, the alcohol component contains an alkylene oxide adduct of bisphenol A, and preferably contains an alkylene oxide adduct of bisphenol A represented by the following formula (I). [ka] [In the formula, OR 1 and R 1 O is an alkylene oxide, and R 1is an alkylene group having 2 or 3 carbon atoms, x and y are positive numbers indicating the average number of moles of alkylene oxide added, and the sum of x and y is preferably 1 or more, more preferably 1.5 or more, and is preferably 16 or less, more preferably 8 or less, and even more preferably 4 or less.

[0023] Examples of the alkylene oxide adduct of bisphenol A represented by formula (I) include a propylene oxide adduct of bisphenol A [2,2-bis(4-hydroxyphenyl)propane] and an ethylene oxide adduct of bisphenol A. These alkylene oxide adducts of bisphenol A can be used alone or in combination of two or more kinds.

[0024] The amount of the alkylene oxide adduct of bisphenol A used is preferably 80 mol % or more, more preferably 90 mol % or more, and 100 mol % or less, based on 100 mol % of the alcohol component of the polyester, in order to improve melt dispersibility in asphalt and obtain excellent rut resistance.

[0025] The alcohol component may contain an alcohol component other than the alkylene oxide adduct of bisphenol A. Examples of the alcohol component include aliphatic diols, aromatic diols (excluding alkylene oxide adducts of bisphenol A), and trihydric or higher polyhydric alcohols. These alcohol components may be used alone or in combination of two or more.

[0026] Examples of the aliphatic diol include ethylene glycol, 1,2-propanediol, 1,3-propanediol, 1,3-butanediol, 1,4-butanediol, 1,4-butenediol, 1,5-pentanediol, 1,6-hexanediol, neopentyl glycol, 1,10-decanediol, and 1,12-dodecanediol. The polyhydric alcohol having a valence of three or more is, for example, a trihydric alcohol. An example of the polyhydric alcohol having a valence of three or more is glycerin.

[0027] <Carboxylic acid component> Examples of the carboxylic acid component include an aliphatic dicarboxylic acid compound, an aromatic dicarboxylic acid compound, and a polyvalent carboxylic acid compound having a valence of 3 to 6. These carboxylic acid components can be used alone or in combination of two or more kinds.

[0028] From the viewpoint of further improving crack resistance, the number of carbon atoms in the main chain of the aliphatic dicarboxylic acid is preferably 3 or more, more preferably 4 or more, and preferably 10 or less, more preferably 8 or less. Examples of the aliphatic dicarboxylic acid compound include fumaric acid, maleic acid, oxalic acid, malonic acid, citraconic acid, itaconic acid, glutaconic acid, succinic acid, adipic acid, suberic acid, azelaic acid, sebacic acid, dodecanedioic acid, succinic acid substituted with an alkyl group having 1 to 20 carbon atoms or an alkenyl group having 2 to 20 carbon atoms, or anhydrides thereof, and alkyl esters thereof (e.g., alkyl groups having 1 to 3 carbon atoms). Examples of the substituted succinic acid include dodecylsuccinic acid, dodecenylsuccinic acid, and octenylsuccinic acid. Among the above aliphatic dicarboxylic acid compounds, at least one selected from the group consisting of fumaric acid, maleic acid, and adipic acid is preferred, and adipic acid is more preferred.

[0029] Examples of aromatic dicarboxylic acid compounds include phthalic acid, terephthalic acid, isophthalic acid, naphthalenedicarboxylic acid, anhydrides thereof, and alkyl esters thereof (for example, alkyl groups having 1 to 3 carbon atoms). Among the above aromatic dicarboxylic acid compounds, isophthalic acid and terephthalic acid are preferred, and terephthalic acid is more preferred, from the viewpoint of obtaining rut resistance.

[0030] The polyvalent carboxylic acid having a valence of 3 to 6 is preferably a trivalent carboxylic acid. Examples of the polyvalent carboxylic acid having a valence of 3 to 6 include trimellitic acid, 2,5,7-naphthalene tricarboxylic acid, pyromellitic acid, and anhydrides thereof. When the polyvalent carboxylic acid is contained, the alcohol component may appropriately contain a monovalent alcohol, and the carboxylic acid component may appropriately contain a monovalent carboxylic acid compound, from the viewpoint of adjusting physical properties.

[0031] When the carboxylic acid component contains an aliphatic dicarboxylic acid compound, the content of the aliphatic dicarboxylic acid compound in the carboxylic acid component is, from the viewpoint of increasing the flexibility of the polyester and further improving the rut resistance, preferably 1 mol % or more, more preferably 3 mol % or more, even more preferably 5 mol % or more, and preferably 15 mol % or less, more preferably 10 mol % or less, based on 100 mol % of the carboxylic acid component.

[0032] From the viewpoint of improving melt dispersibility in asphalt and obtaining excellent rut resistance, the content of the aromatic dicarboxylic acid compound is preferably 60 mol% or more, more preferably 75 mol% or more, and preferably 100 mol% or less, more preferably 99 mol% or less, even more preferably 95 mol% or less, and even more preferably 90 mol% or less, based on 100 mol% of the carboxylic acid component.

[0033] (Molar ratio of structural units derived from carboxylic acid components to structural units derived from alcohol components) The molar ratio of the constituent units derived from the carboxylic acid component to the constituent units derived from the alcohol component [carboxylic acid component / alcohol component] is, from the viewpoints of adjusting the acid value and improving rut resistance, preferably 0.7 or more, more preferably 0.8 or more, even more preferably 0.9 or more, and is preferably 1.5 or less, more preferably 1.3 or less, even more preferably 1.1 or less.

[0034] (Structural unit derived from polyethylene terephthalate) The polyester used in the present invention contains structural units consisting of ethylene glycol and terephthalic acid derived from polyethylene terephthalate. The polyethylene terephthalate may contain small amounts of components such as butanediol and isophthalic acid in addition to the structural units consisting of ethylene glycol and terephthalic acid.

[0035] In recent years, the impact of waste plastics on the environment has become an issue, and recycling of waste plastics has been considered. In the present invention, since polyethylene terephthalate is widely used as products such as bottles and films, polyethylene terephthalate (hereinafter also referred to as "recycled PET") that was produced as such products and then discarded is preferably used from the standpoint of environmental issues and cost. The type of the recycled product is not particularly limited as long as it has a certain degree of purity. It may contain a small amount of plastics such as polyethylene and polypropylene as impurities. For example, waste pouch containers can be used as recycled PET.

[0036] When using the recovered material, it is preferable to use the material crushed into flakes, pellets, etc., for ease of handling, dispersion, and decomposition. The specific size of the recovered material used in the present invention is preferably 4 mm or less from the viewpoint of reaction efficiency. 2 More than 15mm 2 or less, and the thickness is preferably 3 mm or less.

[0037] In the polyester, the molar ratio (B) / (E) of the structural unit (B) derived from an alkylene oxide adduct of bisphenol A to the structural unit (E) consisting of ethylene glycol and terephthalic acid derived from polyethylene terephthalate is, from the viewpoints of storage stability and rut resistance, preferably 30 / 70 or more, more preferably 50 / 50 or more, even more preferably 60 / 40 or more, and is preferably 95 / 5 or less, more preferably 90 / 10 or less, even more preferably 80 / 20 or less. From the viewpoint of storage stability and rut resistance, the (B) / (E) ratio is preferably 30 / 70 or more and 95 / 5 or less, more preferably 50 / 50 or more and 90 / 10 or less, and even more preferably 60 / 40 or more and 80 / 20 or less.

[0038] The polyester used in the present invention may be a polyester modified to such an extent that its properties are not substantially impaired.Specific examples of modified polyesters include polyesters grafted or blocked with phenol, urethane, epoxy, or the like by the methods described in JP-A-11-133668, JP-A-10-239903, JP-A-8-20636, etc.Preferred modified polyesters include urethane-modified polyesters obtained by urethane-extending polyesters with a polyisocyanate compound.

[0039] (Physical properties of polyester) From the viewpoint of obtaining rut resistance, the softening point of the polyester is preferably 90°C or higher, more preferably 95°C or higher, even more preferably 100°C or higher, and preferably 140°C or lower, more preferably 130°C or lower, even more preferably 125°C or lower, still more preferably 120°C or lower, and even more preferably 115°C or lower.

[0040] The acid value of the polyester is preferably 2 mgKOH / g or more, more preferably 3 mgKOH / g or more, and even more preferably 5 mgKOH / g or more, from the viewpoint of promoting adsorption to aggregate and improving rut resistance, and is preferably 40 mgKOH / g or less, more preferably 30 mgKOH / g or less, and even more preferably 20 mgKOH / g or less, from the viewpoint of improving the water resistance of the pavement surface.

[0041] From the viewpoint of improving rut resistance, the hydroxyl value of the polyester is preferably 1 mgKOH / g or more, more preferably 2 mgKOH / g or more, even more preferably 5 mgKOH / g or more, still more preferably 10 mgKOH / g or more, and is preferably 70 mgKOH / g or less, more preferably 50 mgKOH / g or less, even more preferably 30 mgKOH / g or less, still more preferably 26 mgKOH / g or less.

[0042] From the viewpoint of obtaining rut resistance, the glass transition point of the polyester is preferably 30°C or higher, more preferably 40°C or higher, even more preferably 50°C or higher, and is preferably 80°C or lower, more preferably 70°C or lower, even more preferably 65°C or lower.

[0043] The softening point, acid value, hydroxyl value, and glass transition point can be measured by the methods described in the Examples. The softening point, acid value, hydroxyl value, and glass transition point can be adjusted by the raw material monomer composition, molecular weight, catalyst amount, or reaction conditions.

[0044] (Production method of polyester) The method for producing the polyester is not particularly limited, but for example, the polyester can be produced by polycondensing polyethylene terephthalate, an alcohol component containing a bisphenol A alkylene oxide adduct, and a carboxylic acid component. The temperature of the polycondensation reaction is not particularly limited, but is preferably 210° C. or higher and 260° C. or lower from the viewpoints of reactivity and monomer decomposition temperature.

[0045] The amount of polyethylene terephthalate present in the raw material is preferably 4 mass% or more, more preferably 10 mass% or more, even more preferably 13 mass% or more, and is preferably 80 mass% or less, more preferably 70 mass% or less, even more preferably 40 mass% or less, based on 100 mass% of the total amount of polyethylene terephthalate, alcohol components, and carboxylic acid components. The amount of polyethylene terephthalate present in the raw material is preferably 4% by mass or more and 80% by mass or less, more preferably 10% by mass or more and 70% by mass or less, and even more preferably 13% by mass or more and 40% by mass or less, based on 100% by mass of the total amount of polyethylene terephthalate, the alcohol component, and the carboxylic acid component.

[0046] By adding polyethylene terephthalate during the polycondensation reaction between the alcohol component and the carboxylic acid component, an ester exchange reaction occurs, and a polyester can be obtained in which the structural units of polyethylene terephthalate are incorporated into structural units derived from the alcohol component and structural units derived from the carboxylic acid component. The polyethylene terephthalate may be present from the start of the polycondensation reaction, or may be added to the reaction system during the polycondensation reaction. From the viewpoint of rut resistance, the polyethylene terephthalate is preferably added when the reaction rate between the alcohol component and the carboxylic acid component is 10% or less, more preferably 5% or less. The reaction rate refers to the value of the amount of water produced by reaction (mol) / theoretical amount of water produced (mol)×100.

[0047] In the polycondensation reaction, from the viewpoints of reactivity and cost, a tin(II) compound having no Sn-C bond, such as tin(II) di(2-ethylhexanoate), can be used as an esterification catalyst. The amount of the esterification catalyst used is preferably 0.01 parts by mass or more, more preferably 0.2 parts by mass or more, and preferably 3.0 parts by mass or less, more preferably 1.5 parts by mass or less, based on 100 parts by mass of the total amount of the alcohol component, the carboxylic acid component, and the polyethylene terephthalate. In the polycondensation reaction, in addition to the catalyst, a pyrogallol compound such as gallic acid can be used as an esterification promoter from the viewpoints of reactivity and cost. The amount of the esterification promoter used is preferably 0.001 parts by mass or more, more preferably 0.005 parts by mass or more, even more preferably 0.01 parts by mass or more, and preferably 0.50 parts by mass or less, more preferably 0.20 parts by mass or less, and even more preferably 0.10 parts by mass or less, based on 100 parts by mass of the total amount of the alcohol component, the carboxylic acid component, and the polyethylene terephthalate.

[0048] (Polyester content) In the asphalt composition of the present invention, the content of the polyester is, from the viewpoint of improving rut resistance, preferably 0.5 parts by mass, more preferably 1 part by mass or more, even more preferably 3 parts by mass or more, still more preferably 5 parts by mass or more, per 100 parts by mass of asphalt, and is preferably 50 parts by mass or less, more preferably 30 parts by mass or less, even more preferably 20 parts by mass or less, and still more preferably 10 parts by mass or less.

[0049] In the asphalt composition of the present invention, the ratio (P) / (A) of the mass ratio (P) of the polyethylene terephthalate structural units in the polyester to the asphaltene content (A) in the asphalt is, from the viewpoints of rut resistance and storage stability, preferably 0.15 or more, more preferably 0.2 or more, more preferably 0.5 or more, more preferably 0.8, and is preferably 3.5 or less, more preferably 3 or less, and more preferably 2.7 or less.

[0050] [Method of producing asphalt composition] The method for producing the asphalt composition of the present invention preferably includes a step of mixing asphalt with the above-mentioned polyester.

[0051] The asphalt composition can be obtained by heating and melting the asphalt, adding the polyester, and stirring and mixing the components until they are uniformly dispersed in a commonly used mixer. Commonly used mixers include homomixers, dissolvers, paddle mixers, ribbon mixers, screw mixers, planetary mixers, vacuum countercurrent mixers, roll mills, twin-screw extruders, etc.

[0052] The mixing temperature of the asphalt and the polyester is preferably 100°C or higher, more preferably 130°C or higher, even more preferably 160°C or higher, still more preferably 170°C or higher, from the viewpoints of uniformly dispersing the polyester in the asphalt and of rut resistance and storage stability, and is preferably 230°C or lower, more preferably 210°C or lower, even more preferably 200°C or lower, and still more preferably 190°C or lower.

[0053] Furthermore, the mixing time between the asphalt and the polyester is, from the viewpoint of efficiently dispersing the polyester uniformly in the asphalt and of rut resistance and storage stability, preferably 1 minute or 0.1 hour or more, more preferably 0.5 hour or more, even more preferably 1.0 hour or more, still more preferably 1.5 hour or more, and is preferably 10 hours or less, more preferably 7 hours or less, even more preferably 5 hours or less, and still more preferably 3 hours or less.

[0054] From the viewpoints of rut resistance and storage stability, the ratio (P) / (A) of the mass ratio (P) of the polyethylene terephthalate structural units in the polyester to the asphaltene content (A) in the asphalt is preferably 0.15 or more, more preferably 0.2 or more, more preferably 0.5 or more, more preferably 0.8, and is preferably 3.5 or less, more preferably 3 or less, and more preferably 2.7 or less.

[0055] A preferred embodiment of the method for producing an asphalt composition includes a step (step 1) of polycondensing polyethylene terephthalate, an alcohol component containing a bisphenol A alkylene oxide adduct, and a carboxylic acid component in the presence of an esterification catalyst to obtain a polyester, and a step (step 2) of mixing asphalt with the polyester (the polyester obtained in step 1). Includes.

[0056] The polyethylene terephthalate is preferably a recovered polyethylene terephthalate. In this case, the method for producing the asphalt composition preferably includes a step of recovering the polyethylene terephthalate from a product (step 1a), a step of polycondensing the polyethylene terephthalate (obtained in step 1a) and an alcohol component containing a bisphenol A alkylene oxide adduct and a carboxylic acid component in the presence of an esterification catalyst to obtain a polyester (step 2a), and a step of mixing the asphalt with the polyester (obtained in step 2a) (step 3a).

[0057] [Dispersant] The asphalt composition may include a dispersant. The dispersant is preferably one which dissolves in asphalt and has affinity with polyester. Examples of the dispersant include polymer dispersants, and surfactants such as polyoxyethylene alkylamines and alkanolamines. Examples of polymer dispersants include polyamidoamines and their salts, polycarboxylic acids and their salts, high molecular weight unsaturated acid esters, modified polyurethanes, modified polyesters, modified poly(meth)acrylates, (meth)acrylic copolymers, naphthalenesulfonic acid-formalin condensates, etc. These dispersants may be used alone or in combination of two or more. The dispersant is preferably a polymer dispersant from the viewpoint of improving high-temperature storage stability. In the present invention, the "polymer dispersant" means a dispersant having a weight-average molecular weight of 1,000 or more. Although it depends on the type of polymer, the weight-average molecular weight is preferably 2,000 or more, more preferably 4,000 or more, and is preferably 80,000 or less, more preferably 40,000 or less.

[0058] The dispersant preferably has a basic functional group. The basic functional group means a group whose conjugate acid has a pKa of -3 or more. Examples of the basic functional group include an amino group, an imino group, and a quaternary ammonium group. From the viewpoint of high-temperature storage stability, the base number of the dispersant is preferably 10 mgKOH / g or more, more preferably 20 mgKOH / g or more, even more preferably 30 mgKOH / g or more, and is preferably 150 mgKOH / g or less, more preferably 120 mgKOH / g or less, even more preferably 100 mgKOH / g or less. The base number is measured by the method specified in JIS K7237:1995.

[0059] Commercially available dispersants include, for example, the "Disper" series of "byk-101", "byk-130", "byk-161", "byk-162", "byk-170", "byk-2020", "byk-2164", and "byk-LPN21324" (all manufactured by BYK); the "Solsperse" series of "9000", "11200", "13240", "13650", "13940", "17000", "18000", "24000", "28000", and "32000"; These include "38500" and "71000" (all manufactured by Lubrizol); "Ajisper" series "PB821", "PB822", "PB880", and "PB881" (all manufactured by Ajinomoto Fine-Techno Co., Ltd.); "Fuka" series "46", "47", "48", "49", "4010", "4047", "4050", "4165", and "5010" (all manufactured by BASF); "Floren TG-710" (manufactured by Kyoeisha Chemical Co., Ltd.); and "TAMN-15" (manufactured by Nikko Chemicals Co., Ltd.).

[0060] From the viewpoint of high-temperature storage stability, the content of the dispersant is, relative to 100 parts by mass of the polyester, preferably 1 part by mass or more, more preferably 3 parts by mass or more, even more preferably 4 parts by mass or more, and preferably 80 parts by mass or less, more preferably 60 parts by mass or less, even more preferably 40 parts by mass or less, still more preferably 30 parts by mass or less, and even more preferably 20 parts by mass or less.

[0061] [Asphalt mixture] The asphalt composition of the present invention is a binder composition, and is used for paving after adding aggregate to the asphalt composition to form an asphalt mixture. That is, the asphalt composition of the present invention is suitable for paving, and is particularly suitable for road paving. The asphalt mixture of the present invention contains the above-mentioned asphalt composition and aggregate. That is, the asphalt mixture contains asphalt, polyester and aggregate, and preferably contains asphalt, thermoplastic elastomer, polyester and aggregate.

[0062] From the viewpoint of improving rut resistance, the content of the asphalt composition in the asphalt mixture is preferably 2 mass% or more, more preferably 3 mass% or more, even more preferably 4 mass% or more, and preferably 15 mass% or less, more preferably 10 mass% or less, even more preferably 8 mass% or less, based on 100 mass% of the asphalt mixture.

[0063] 〔aggregate〕 The aggregate may be any material selected from crushed stone, boulders, gravel, sand, recycled aggregate, ceramics, etc. In addition, the aggregate may be either coarse aggregate with a particle size of 2.36 mm or more, or fine aggregate with a particle size of less than 2.36 mm. Examples of coarse aggregate include crushed stone with a particle size range of 2.36 mm to 4.75 mm, crushed stone with a particle size range of 4.75 mm to 12.5 mm, crushed stone with a particle size range of 12.5 mm to 19 mm, and crushed stone with a particle size range of 19 mm to 31.5 mm. The fine aggregate is preferably one having a particle size of 0.075 mm or more and less than 2.36 mm. Examples of fine aggregate include river sand, dune sand, mountain sand, sea sand, crushed sand, fine sand, screenings, crushed stone dust, silica sand, artificial sand, glass cullet, foundry sand, and recycled crushed aggregate sand. The above particle size is the value specified in JIS A5001:1995. Among these, a combination of coarse aggregate and fine aggregate is preferable.

[0064] The fine aggregate may contain a filler (such as sand) having a particle size of less than 0.075 mm. Examples of the filler include sand, fly ash, calcium carbonate, hydrated lime, etc. Among these, calcium carbonate is preferred from the viewpoint of improving dry strength.

[0065] From the viewpoint of improving dry strength, the average particle size of the filler is preferably 0.001 mm or more, and preferably 0.05 mm or less, more preferably 0.03 mm or less, and further preferably 0.02 mm or less. The average particle size of the filler can be measured by a laser diffraction particle size distribution measuring device. Here, the average particle size means the average particle size at 50% cumulative volume.

[0066] [Method of measuring average particle size of filler] The average particle size of the filler was measured using a laser diffraction particle size distribution measuring device "LA-950" (manufactured by Horiba, Ltd.) under the conditions shown below. Measurement method: Flow method Dispersion medium: Ethanol Sample preparation: 2mg / 100mL Dispersion method: Stirring, built-in ultrasonic 1 minute

[0067] From the viewpoint of rut resistance, the mass ratio of coarse aggregate to fine aggregate is preferably 10 / 90 or more, more preferably 20 / 80 or more, even more preferably 30 / 70 or more, and is preferably 90 / 10 or less, more preferably 80 / 20 or less, even more preferably 70 / 30 or less.

[0068] From the viewpoint of rut resistance, the content of the aggregate is preferably 1,000 parts by mass or more, more preferably 1,200 parts by mass or more, and even more preferably 1,400 parts by mass or more, per 100 parts by mass of the asphalt composition, and is preferably 3,000 parts by mass or less, more preferably 2,500 parts by mass or less, and even more preferably 2,000 parts by mass or less.

[0069] A suitable example of the blend for the asphalt mixture is as follows: (1) An example asphalt mixture includes, for example, 30% to less than 45% by volume of coarse aggregate, 30% to 50% by volume of fine aggregate, and 5% to 10% by volume of an asphalt composition (fine-grained asphalt). (2) An example asphalt mixture includes, for example, 45% to less than 70% by volume of coarse aggregate, 20% to 45% by volume of fine aggregate, and 3% to 10% by volume of an asphalt composition (dense-graded asphalt). (3) An example of an asphalt mixture includes, for example, 70% by volume or more and 80% by volume or less of coarse aggregate, 10% by volume or more and 20% by volume or less of fine aggregate, and 3% by volume or more and 10% by volume or less of an asphalt composition (porous asphalt).

[0070] The asphalt mixture may further contain other components as required. The proportion of asphalt in conventional asphalt mixtures containing aggregate and asphalt is usually determined based on the optimal amount of asphalt obtained from the "Mix Design of Asphalt Composition" described in the "Guidelines for Pavement Design and Construction" issued by the Japan Road Association. In the present invention, the above-mentioned optimum asphalt amount corresponds to the total amount of asphalt, thermoplastic elastomer and polyester. Therefore, it is usually preferable that the optimum asphalt amount is the total amount of asphalt, thermoplastic elastomer and polyester. However, it is not necessary to be limited to the method described in the "Guidelines for Pavement Design and Construction" and other methods may be used to determine the method.

[0071] [Asphalt mixture manufacturing method] The method for producing an asphalt mixture of the present invention includes a step (step 1) of obtaining a polyester by polycondensation reaction of polyethylene terephthalate, an alcohol component containing a bisphenol A alkylene oxide adduct, and a carboxylic acid component in the presence of an esterification catalyst, and a step (step 2) of mixing heated aggregate, asphalt, and the polyester (the polyester obtained in step 1), and preferably includes a step of mixing heated aggregate, asphalt, a thermoplastic elastomer, and the polyester.

[0072] Specific methods for producing asphalt mixtures include conventional methods for producing asphalt mixtures called the plant mix method and the premix method. All of these methods involve adding asphalt (and thermoplastic elastomer, if necessary) and polyester to heated aggregate. Examples of the addition method include the premix method in which asphalt (and thermoplastic elastomer, if necessary) and polyester are dissolved in advance, or the plant mix method in which modified asphalt in which thermoplastic elastomer is dissolved in asphalt is added, and then polyester is added. Among these, the premix method is preferred from the viewpoint of rut resistance. More specifically, in the method for producing an asphalt mixture, in the mixing step, preferably, (i) adding and mixing asphalt (and thermoplastic elastomer, if necessary) to the heated aggregate, and then adding and mixing polyester; (ii) adding and mixing the asphalt (and optionally the thermoplastic elastomer) and polyester simultaneously to the heated aggregate; or (iii) A pre-heat mixed mixture of asphalt (and optionally thermoplastic elastomer) and polyester is added to and mixed with the heated aggregate. Among these, method (iii) is preferred from the viewpoint of rut resistance.

[0073] The mixing temperature when the asphalt and the polyester are mixed in advance in the method (iii) is preferably a temperature higher than the softening point of the polyester from the viewpoint of rut resistance, and is preferably 130°C or higher, more preferably 150°C or higher, even more preferably 170°C or higher, and even more preferably 180°C or higher, and from the viewpoint of preventing thermal degradation of the asphalt, is preferably 230°C or lower, more preferably 210°C or lower, and even more preferably 200°C or lower. The mixing time is, for example, 10 minutes or more, preferably 30 minutes or more, more preferably 1 hour or more, and more preferably 2 hours or more. The upper limit of the time is not particularly limited, but is, for example, about 5 hours.

[0074] The temperature of the heated aggregate in methods (i) to (iii) is preferably higher than the softening point of the polyester from the viewpoint of rut resistance, and is preferably 130°C or higher, more preferably 150°C or higher, even more preferably 170°C or higher, and even more preferably 180°C or higher, and from the viewpoint of preventing thermal degradation of the asphalt, is preferably 230°C or lower, more preferably 210°C or lower, and even more preferably 200°C or lower.

[0075] In the mixing step, from the viewpoint of rut resistance, the mixing temperature is preferably higher than the softening point of the polyester, preferably 130° C. or higher, more preferably 150° C. or higher, even more preferably 170° C. or higher, and even more preferably 180° C. or higher, and from the viewpoint of preventing thermal degradation of the asphalt, it is preferably 230° C. or lower, more preferably 210° C. or lower, and even more preferably 200° C. or lower. The mixing time in the mixing step is, for example, 30 seconds or more, preferably 1 minute or more, more preferably 2 minutes or more, and even more preferably 5 minutes or more, and the upper limit of the time is not particularly limited, but is, for example, about 30 minutes.

[0076] From the viewpoint of improving rut resistance, the method for producing an asphalt mixture preferably includes, after the mixing step, a step of holding the resulting mixture at a temperature higher than the softening point of the polyester. In the holding step, the mixture may be further mixed, but it is sufficient that the mixture is held at the aforementioned temperature or higher. In the holding step, the mixing temperature is preferably higher than the softening point of the polyester, and is preferably 130° C. or higher, more preferably 150° C. or higher, even more preferably 170° C. or higher, and even more preferably 180° C. or higher, and from the viewpoint of preventing thermal deterioration of the asphalt composition, is preferably 230° C. or lower, more preferably 210° C. or lower, and even more preferably 200° C. or lower. The holding time in the holding step is preferably 0.5 hours or longer, more preferably 1 hour or longer, and even more preferably 1.5 hours or longer, and the upper limit of the time is not particularly limited, but is, for example, about 5 hours.

[0077] The polyethylene terephthalate is preferably recovered polyethylene terephthalate. In this case, the method for producing an asphalt mixture includes a step of recovering polyethylene terephthalate from a product (step 1a), a step of polycondensing the polyethylene terephthalate (obtained in step 1a) and an alcohol component containing a bisphenol A alkylene oxide adduct and a carboxylic acid component in the presence of an esterification catalyst to obtain a polyester (step 2a), and a step of mixing a heated aggregate, asphalt, and the polyester (obtained in step 2a) (step 3a).

[0078] [Road paving method] The asphalt mixture of the present invention is suitable for road paving, and as described above, an asphalt mixture obtained by adding aggregate to an asphalt composition is used for road paving. The road paving method preferably includes a step of applying the asphalt mixture to a road to form an asphalt pavement layer. Specifically, the road paving method includes a step (step 1) of obtaining an asphalt mixture by mixing asphalt, the polyester, and aggregate, and a step (step 2) of applying the asphalt mixture obtained in step 1 to a road to form an asphalt pavement layer. The asphalt pavement layer is preferably a base layer or a surface layer.

[0079] The asphalt mixture may be compacted and applied in a similar manner using a known construction machine. The compaction temperature when used as a heated asphalt mixture is preferably higher than the softening point of polyester from the viewpoint of rut resistance, and is preferably 100°C or higher, more preferably 120°C or higher, even more preferably 130°C or higher, and is preferably 200°C or lower, more preferably 180°C or lower.

[0080] The present invention further comprises the following: <1> ~ <7> Disclose <1> An asphalt composition comprising asphalt and a polyester, The asphalt composition, wherein the polyester is a polycondensate of polyethylene terephthalate, an alcohol, and a carboxylic acid compound, and the alcohol comprises an alkylene oxide adduct of bisphenol A. <2> the molar ratio (B) / (E) of the structural unit (B) derived from the alkylene oxide adduct of bisphenol A to the structural unit (E) composed of ethylene glycol and terephthalic acid derived from the polyethylene terephthalate in the polyester is 30 / 70 or more and 95 / 5 or less, and the acid value of the polyester is 2 mgKOH / g or more and 40 mgKOH / g or less. <1> The asphalt composition according to claim 1. <3> the molar ratio (B) / (E) of the structural unit (B) derived from the alkylene oxide adduct of bisphenol A to the structural unit (E) consisting of ethylene glycol and terephthalic acid derived from the polyethylene terephthalate in the polyester is 50 / 50 or more and 95 / 5 or less, and the acid value of the polyester is 2 mgKOH / g or more and 40 mgKOH / g or less. <1> The asphalt composition according to claim 1. <4> the molar ratio (B) / (E) of the structural unit (B) derived from the alkylene oxide adduct of bisphenol A to the structural unit (E) consisting of ethylene glycol and terephthalic acid derived from the polyethylene terephthalate in the polyester is 30 / 70 or more and 80 / 20 or less, and the acid value of the polyester is 2 mgKOH / g or more and 40 mgKOH / g or less. <1> The asphalt composition according to claim 1. <5> the molar ratio (B) / (E) of the structural unit (B) derived from the alkylene oxide adduct of bisphenol A to the structural unit (E) consisting of ethylene glycol and terephthalic acid derived from the polyethylene terephthalate in the polyester is 30 / 70 or more and 95 / 5 or less, and the acid value of the polyester is 5 mgKOH / g or more and 40 mgKOH / g or less; <1> The asphalt composition according to claim 1. <6> the molar ratio (B) / (E) of the structural unit (B) derived from the alkylene oxide adduct of bisphenol A to the structural unit (E) consisting of ethylene glycol and terephthalic acid derived from the polyethylene terephthalate in the polyester is 30 / 70 or more and 95 / 5 or less, and the acid value of the polyester is 2 mgKOH / g or more and 30 mgKOH / g or less. <1> The asphalt composition according to claim 1. <7> the molar ratio (B) / (E) of the structural unit (B) derived from the alkylene oxide adduct of bisphenol A to the structural unit (E) composed of ethylene glycol and terephthalic acid derived from the polyethylene terephthalate in the polyester is 60 / 40 or more and 80 / 20 or less, and the acid value of the polyester is 5 mgKOH / g or more and 20 mgKOH / g or less. <1> The asphalt composition according to claim 1. EXAMPLES

[0081] The physical properties of the resin and the like were measured and evaluated by the following methods. [Measurement method] [Acid value and hydroxyl value of polyester] The acid value and hydroxyl value of the polyester were measured according to the method of JIS K0070: 1992. However, the measurement solvent was changed from the mixed solvent of ethanol and ether specified in JIS K0070: 1992 to a mixed solvent of acetone and toluene (acetone:toluene = 1:1 (volume ratio)).

[0082] [Softening point and glass transition point of polyester] (1) Softening point Using a flow tester "CFT-500D" (Shimadzu Corporation), 1 g of the sample was heated at a temperature increase rate of 6°C / min, while applying a load of 1.96 MPa with the plunger, and extruding the sample from a nozzle with a diameter of 1 mm and a length of 1 mm. The plunger descent amount of the flow tester was plotted against the temperature, and the temperature at which half of the sample flowed out was taken as the softening point. (2) Glass transition temperature Using a differential scanning calorimeter "Q-100" (manufactured by TA Instruments Japan Co., Ltd.), 0.01 to 0.02 g of the sample was weighed into an aluminum pan, heated to 200°C, and cooled from that temperature to 0°C at a rate of 10°C / min. Measurements were then taken while heating to 150°C at a rate of 10°C / min. The glass transition point was determined as the temperature at the intersection of an extension of the baseline below the maximum endothermic peak temperature and a tangent line showing the maximum slope from the rising part of the peak to the apex of the peak.

[0083] Manufacturing Examples 1 to 6 (Production of Polyester Resins (A1) to (A4) and (a1) to (a2)) The alcohol component, carboxylic acid component and PET of the polyester shown in Table 1 were placed in a 5-liter four-neck flask equipped with a thermometer, a stainless steel stirring rod, a downflow condenser and a nitrogen inlet tube, and the amounts of tin(II) di(2-ethylhexanoate) and gallic acid shown in Table 1 were added in a nitrogen atmosphere. The temperature was raised to 235°C over 3 hours in a mantle heater, and the temperature was maintained for 5 hours after reaching 235°C. After confirming with the naked eye that the PET particles had disappeared from the reaction product, the reaction was carried out under reduced pressure at 8.0 kPa, and the reaction was continued until the softening point shown in Table 1 was reached, thereby obtaining the target polyester resins (A1) to (A4) and (a1) to (a2).

[0084] [Table 1]

[0085] Example 1 As a binder mixture, 2,200 g of modified type II asphalt (manufactured by Toa Road Industry Co., Ltd., asphaltene concentration in asphalt: 15% by mass) heated to 180°C was placed in a 3 L stainless steel container and stirred at 100 rpm, and 110 g of polyester resin (A1) (5 parts by mass per 100 parts by mass of asphalt) was gradually added and stirred at 300 rpm for 2 hours to produce an asphalt composition (AS-1).

[0086] Next, 11 kg of aggregate heated to 180°C (see below for the composition of the aggregate) was placed in an asphalt mixer and mixed at 180°C for 60 seconds. Next, 635 g of the asphalt composition (AS-1) was added and mixed for 2 minutes with an asphalt mixer. The resulting asphalt mixture was stored at 180°C for 2 hours, then filled into a 300 x 300 x 50 mm formwork, and subjected to a pressure treatment of 25 revolutions at a temperature of 150°C and a load of 0.44 kPa using a roller compactor (manufactured by Iwata Kogyosho Co., Ltd.) to prepare an asphalt mixture (M-1) as a test specimen.

[0087] <Aggregate composition> No. 6 crushed stone 50.9 parts by weight Crushed sand 1 10.4 parts by mass Crushed sand 2 22.1 parts by mass Fine sand 10.4 parts by mass Stone powder 6.2 parts by mass Passed mass%: Sieve size 15 mm: 100% by mass Sieve size 10 mm: 85.6% by mass Sieve size 5 mm: 49.7% by mass Sieve size 2.5 mm: 44.6% by mass Sieve size 1.2 mm: 31.6% by mass Sieve size 0.6 mm: 21.3% by mass Sieve size 0.3 mm: 12.7% by mass Sieve size 0.15mm: 7.1% by mass

[0088] Examples 2 to 4 Asphalt compositions (AS-2) to (AS-4) were prepared in the same manner as in Example 1, except that the polyester resin (A1) in Example 1 was changed to polyester resins (A2) to (A4), respectively. In Example 1, 635 g of the asphalt composition (AS-1) was replaced with 635 g of each of the asphalt compositions (AS-2) to (AS-4), respectively. The same procedure as in Example 1 was repeated to obtain asphalt mixtures (M-2) to (M-4) as specimens.

[0089] Example 5 An asphalt composition (AS-5) was obtained in the same manner as in Example 1, except that the amount of polyester resin (A1) added was changed to 550 g (25 parts by mass per 100 parts by mass of asphalt). An asphalt mixture (M-5) was obtained as a specimen in the same manner as in Example 1, except that 635 g of the asphalt composition (AS-1) was changed to 756 g of the asphalt composition (AS-5).

[0090] Example 6 An asphalt composition (AS-6) was obtained in the same manner as in Example 1, except that the asphalt in Example 1 was changed to straight asphalt (manufactured by Toa Road Industry Co., Ltd., asphaltene concentration in asphalt: 15 mass%). An asphalt mixture (M-6) was obtained as a specimen in the same manner as in Example 1, except that 635 g of the asphalt composition (AS-1) in Example 1 was changed to 635 g of the asphalt composition (AS-6).

[0091] Example 7 An asphalt composition (AS-7) was obtained in the same manner as in Example 1, except that the asphalt in Example 1 was changed to modified asphalt "PG76-22" (Ergon Corporation, Texas, USA, asphaltene concentration in asphalt: 22% by mass). An asphalt mixture (M-7) was obtained as a specimen in the same manner as in Example 1, except that 635 g of the asphalt composition (AS-1) in Example 1 was changed to 635 g of the asphalt composition (AS-7).

[0092] Example 8 An asphalt composition (AS-8) was obtained in the same manner as in Example 3, except that in Example 1, the asphalt was changed to a modified asphalt (manufactured by FESPA, Mexico; asphaltene concentration in asphalt: 28 mass%). An asphalt mixture (M-8) was obtained as a specimen in the same manner as in Example 1, except that 635 g of the asphalt composition (AS-1) in Example 1 was changed to 635 g of the asphalt composition (AS-8).

[0093] Example 9 An asphalt mixture (M-9) was obtained as a test specimen in the same manner as in Example 1, except that 635 g of the asphalt composition (AS-1) was changed to 716 g of the asphalt composition (AS-1).

[0094] Example 10 An asphalt mixture (M-10) was obtained as a specimen in the same manner as in Example 1, except that 635 g of the asphalt composition (AS-1) was changed to 520 g of the asphalt composition (AS-1).

[0095] Comparative Example 1 In Example 1, the polyester resin (A1) was not added, and the modified type II asphalt was used as it was. An asphalt mixture (MA) was obtained as a test specimen in the same manner as in Example 1, except that 635 g of the asphalt composition (AS-1) was changed to 605 g of modified type II asphalt.

[0096] Comparative Examples 2 to 3 Asphalt compositions (AS-a1) to (AS-a2) were prepared in the same manner as in Example 1, except that the polyester resin (A1) in Example 1 was changed to polyester resins (a1) to (a2), respectively. In Example 1, 635 g of asphalt composition (AS-1) was changed to 635 g of asphalt compositions (AS-a1) to (AS-a2), respectively, and the same procedure as in Example 1 was repeated to obtain asphalt mixtures (M-a1) to (M-a2) as test specimens.

[0097] Comparative Example 4 An asphalt composition (AS-a3) was prepared in the same manner as in Example 1, except that the polyester resin (A1) in Example 1 was changed to PET1 ("RAMAPET L1", manufactured by Indorama Ventures). An asphalt mixture (M-a3) was obtained as a specimen in the same manner as in Example 1, except that 635 g of the asphalt composition (AS-1) in Example 1 was changed to 635 g of the asphalt composition (AS-a3).

[0098] [evaluation] [Rutting resistance] The specimen was immersed in hot water set at 60°C in a 60°C thermostatic chamber, and a wheel tracking tester (manufactured by Iwata Kogyosho Co., Ltd., load 1370N, iron wheel width 47mm, linear pressure 291.5N / cm) was used to move the wheel back and forth over the specimen at a speed of 15 times / min, measuring the amount of displacement at 1,250 and 2,500 passes. Other measurement conditions were in accordance with the "B003 Wheel Tracking Test" described in the "Pavement Survey and Test Method Handbook" published by the Japan Road Association. In Examples 1 to 5, 7 to 10 and Comparative Examples 1 to 4 using modified asphalt, the test specimen was immersed in hot water set to 60°C in a 60°C thermostatic chamber, and the amount of displacement was measured after 2,500 tire passes. In Example 6 using straight asphalt, the test specimen was immersed in hot water set to 50°C in a 50°C thermostatic chamber, and the amount of displacement was measured after 1,250 tire passes. The results are shown in Table 2.

[0099] [Storage stability of asphalt composition] 50 mL of the asphalt composition was poured into a sample bottle (inner diameter 3.5 cm x height 7.8 cm) and stored in a 180°C oven for 4 hours, after which the height of the polyester precipitate in the asphalt composition was measured. The percentage of the height of the precipitate that had occurred relative to the height of the precipitate if all of the polyester in the asphalt had precipitated was calculated and used as an index of storage stability. The lower the value, the less the amount of precipitation and the better the storage stability. For Comparative Example 1, which did not contain polyester, no measurement was performed because no precipitation of polyester occurred. In the table, this is indicated by "-".

[0100] [Table 2]

[0101] Comparative Example 2, which does not contain structural units consisting of ethylene glycol and terephthalic acid derived from polyethylene terephthalate, is capable of suppressing rutting but has poor storage stability of asphalt at high temperatures.On the other hand, Comparative Example 4, which contains polyethylene terephthalate as is, and Comparative Example 3, which does not contain structural units derived from an alkylene oxide adduct of bisphenol A, are unable to sufficiently suppress rutting. In contrast, according to the present invention, an asphalt composition containing a specific polyester that includes structural units consisting of ethylene glycol and terephthalic acid derived from polyethylene terephthalate and structural units derived from an alkylene oxide adduct of bisphenol A has excellent storage stability and is able to further suppress rutting on the pavement surface after construction.

Claims

1. An asphalt composition comprising asphalt and a polyester, The polyester is a polycondensation product of polyethylene terephthalate, an alcohol and a carboxylic acid compound, and the alcohol contains an alkylene oxide adduct of bisphenol A. fruit, In the polyester, a molar ratio (B) / (E) of a structural unit (B) derived from an alkylene oxide adduct of bisphenol A to a structural unit (E) composed of ethylene glycol and terephthalic acid derived from the polyethylene terephthalate is 30 / 70 or more and 95 / 5 or less; The content of the polyester is 0.5 parts by mass or more and 50 parts by mass or less per 100 parts by mass of asphalt, and An asphalt composition, wherein the ratio (P) / (A) of the mass ratio (P) of the constituent units derived from the polyethylene terephthalate in the polyester to the content (A) of asphaltene in the asphalt is 0.15 or more and 3.5 or less.

2. 2. The asphalt composition of claim 1, wherein the polyethylene terephthalate is reclaimed polyethylene terephthalate.

3. The asphalt composition according to claim 1 or 2, wherein the acid value of the polyester is from 2 mg KOH / g to 40 mg KOH / g.

4. The asphalt composition according to any one of claims 1 to 3, further comprising a thermoplastic elastomer.

5. The asphalt composition according to claim 4, wherein the thermoplastic elastomer is at least one selected from the group consisting of styrene / butadiene block copolymers, styrene / butadiene / styrene block copolymers, styrene / butadiene random copolymers, styrene / isoprene block copolymers, styrene / isoprene / styrene block copolymers, styrene / isoprene random copolymers, ethylene / vinyl acetate copolymers, and ethylene / acrylic acid ester copolymers.

6. Step 1: A step of subjecting polyethylene terephthalate, an alcohol component containing a bisphenol A alkylene oxide adduct, and a carboxylic acid component to a polycondensation reaction in the presence of an esterification catalyst to obtain a polyester; and Step 2: Mixing asphalt with the polyester obtained in step 1 Including, In the polyester, a molar ratio (B) / (E) of a structural unit (B) derived from an alkylene oxide adduct of bisphenol A to a structural unit (E) composed of ethylene glycol and terephthalic acid derived from the polyethylene terephthalate is 30 / 70 or more and 95 / 5 or less; The polyester is 0.5 parts by mass or more and 50 parts by mass or less per 100 parts by mass of asphalt, and A method for producing an asphalt composition, wherein the ratio (P) / (A) of the mass ratio (P) of the constituent units derived from the polyethylene terephthalate in the polyester to the content (A) of asphaltene in the asphalt is 0.15 or more and 3.5 or less.

7. The method for producing an asphalt composition according to claim 6, wherein the polyethylene terephthalate is recycled polyethylene terephthalate.

8. An asphalt mixture comprising the asphalt composition according to any one of claims 1 to 5 and aggregate.

9. Step 1: A step of subjecting polyethylene terephthalate, an alcohol component containing a bisphenol A alkylene oxide adduct, and a carboxylic acid component to a polycondensation reaction in the presence of an esterification catalyst to obtain a polyester; and Step 2: Mixing the heated aggregate, asphalt, and the polyester obtained in step 1 Including, In the polyester, a molar ratio (B) / (E) of a structural unit (B) derived from an alkylene oxide adduct of bisphenol A to a structural unit (E) composed of ethylene glycol and terephthalic acid derived from the polyethylene terephthalate is 30 / 70 or more and 95 / 5 or less; The polyester is 0.5 parts by mass or more and 50 parts by mass or less per 100 parts by mass of asphalt, and A method for producing an asphalt mixture, wherein a ratio (P) / (A) of a mass ratio (P) of a constituent unit derived from the polyethylene terephthalate in the polyester to a content (A) of asphaltene in the asphalt is 0.15 or more and 3.5 or less.

10. In the mixing step in step 2, (i) adding and mixing asphalt to the heated aggregate, and then adding and mixing polyester; (ii) adding and mixing the asphalt and polyester simultaneously to the heated aggregate; or (iii) adding and mixing the pre-heat mixed asphalt and polyester mixture with the heated aggregate; The method for producing an asphalt mixture according to claim 9.

11. The method for producing an asphalt mixture according to claim 9 or 10, wherein the polyethylene terephthalate is recycled polyethylene terephthalate.

Citation Information

Patent Citations

  • Method for producing plastic composition for pavement material

    JP2006096799A

  • Electrostatic charge image developing toner

    JP2009276791A

  • Asphalt mixture

    JP2020200459A

  • Asphalt composition for road pavement

    WO2017125421A1

  • Asphalt composition

    WO2019017334A1